Circadian rhythms of sexual activities in moths: a review - Groot, Astrid T. (Frontiers in Ecology and Evolution, 2014)
The circadian rhythm of behavior has interested many researchers in the past decades, yet amazingly little is known on the evolution of natural variation in circadian rhythms of behavior. Most research has been focused on identifying the circadian clock genes that form an intricate clock network, which turns out to be more complex with every discovery. To understand the importance of circadian rhythms of behavior in speciation, genetic analyses should be conducted on intra- and interspecific allochronic differentiation of behaviors. Many moth species show specific daily activity rhythms in their sexual activities, some species being sexually active early at night, while others are sexually active late at night. This differentiation has been suggested to have arisen to minimize communication interference between closely related species, as co-occurring and closely related species with overlapping sex pheromone blends show a temporal differentiation in their daily sexual activities. However, the genetic differentiation of this allochronic separation has barely been examined in any species so far. In this review I summarize studies conducted on timing of sexual activities in moths, and which factors have been found to influence this timing, with the aim to identify the gaps and challenges, to unravel the possible contribution of allochronic differentiation of sexual activities in moth speciation.